Enhancing Learning Engagement of Students with Special Needs through Inclusive Classroom Management Strategies - Yuliana, Yuliana; Sukinah, Sukinah (Papanda Publisher, 2025)
Students with special needs in inclusive early childhood education settings often experience reduced learning engagement and participation, challenging educators to develop effective classroom management strategies that accommodate diverse learning needs while maintaining quality instruction for all students. This qualitative descriptive study investigated inclusive classroom management strategies at State Kindergarten 1 Long Mesangat, Indonesia, from March to June 2025. Data collection employed participatory observation, in-depth interviews with teachers and administrators, and documentary analysis. Participants included students with special needs, classroom teachers, special education support teachers (GPK), school principal, and parents. Data analysis followed Miles and Huberman's interactive model involving data reduction, display, and conclusion drawing with verification through triangulation techniques. Findings revealed that systematic implementation of differentiated instruction, concrete learning materials, visual aids, and collaborative teaching models significantly enhanced learning interest among students with special needs. Students demonstrated improved attention spans (82% of cases), increased voluntary participation (78%), and more positive learning behaviors (75%). Special education support teachers provided crucial interventions averaging 8-15 individual assistance sessions daily. However, implementation challenges included insufficient specialized teacher training, limited adaptive resources, and inadequate family engagement in supporting inclusive practices. The study confirms that comprehensive inclusive classroom management strategies effectively enhance student engagement when supported by collaborative teaching models and appropriate resources. Findings align with Universal Design for Learning principles and evidence-based classroom management practices. However, persistent systemic barriers including teacher preparation gaps and resource limitations continue to impede optimal implementation. Systematic inclusive classroom management strategies can meaningfully improve learning outcomes for students with special needs in early childhood settings. Success requires addressing teacher preparation deficits, expanding specialized support personnel, and strengthening family-school collaboration through policy and professional development initiatives.